2020
DOI: 10.1002/alr.22610
|View full text |Cite
|
Sign up to set email alerts
|

Smell and taste alterations in COVID‐19: a cross‐sectional analysis of different cohorts

Abstract: Background: Olfactory (OD) and gustatory (GD) dysfunction have been proven to be a typical symptom of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection. However, their prevalence in different patient populations still needs to be clarified. Methods: A cross-sectional study was performed from March 27 to April 1, 2020, in Northern Italy. Physicians administered a survey-based questionnaire to SARS-CoV-2positive patients with the aim of assessing symptoms, focusing on OD and GD. Two groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
2
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 30 publications
12
104
2
10
Order By: Relevance
“…18,20,[24][25][26]29,32,34,37,[40][41][42][43][47][48][49][50][51][52][53][54][55][56][57][58][59] The remaining studies assessed olfactory ability through anamnestic data collection, simple surveys and/or structured, non-validated questionnaires (Table 4). 2,16,17,19,[21][22][23]27,28,30,31,33,35,36,38,39,[44][45][46]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20,[24][25][26]29,32,34,37,[40][41][42][43][47][48][49][50][51][52][53][54][55][56][57][58][59] The remaining studies assessed olfactory ability through anamnestic data collection, simple surveys and/or structured, non-validated questionnaires (Table 4). 2,16,17,19,[21][22][23]27,28,30,31,33,35,36,38,39,[44][45][46]…”
Section: Resultsmentioning
confidence: 99%
“…61 Regarding the hospital setting, our review highlighted a lower prevalence of smell disorders in hospitalised patients compared with home-quarantined patients. Two studies focused specifically on this comparison, 2,35 emphasising a greater prevalence of the disorder in individuals with low-to-mild disease compared to those who needed hospital treatment. Once again, this difference could be related to greater attention devoted to olfactory impairment in patients in an overall better health condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of olfactory and gustatory disturbance in our local COVID-19 cohort is consistent with the results of a metaanalysis of 10 large cohort studies of smell impairment and nine large cohort studies of taste impairment, respectively, which showed a prevalence of 52.5% and 43.93% of olfactory and gustatory dysfunction. 20 However, some individual cohorts display the opposite trend, with a higher prevalence of gustatory than olfactory impairment, 21,22 which cannot be explained solely by regional differences in viral load in the pharynx.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are some reports that COVID-19 patients experience a period of anosmia and/or ageusia without any other symptoms (Hummel, Landis, & Huttenbrink, 2011;Karimi-Galougahi, Raad, & Mikaniki, 2020). Olfactory and taste dysfunction have very recently been reported to be higher in home-quarantined, young, and female patients (Paderno et al, 2020). Screening for loss of taste or smell in otherwise asymptomatic individuals may be an effective strategy to stop transmission early in the disease.…”
Section: Introductionmentioning
confidence: 99%